2015
DOI: 10.2106/jbjs.n.01100
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification with Chemically Modified Synovial Fluid for Flexor Tendon Reconstruction in a Canine Model in Vivo

Abstract: Background: Functional restoration is the major concern after flexor tendon reconstruction in the hand. The purpose of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…While surgical repair serves as the standard procedure for flexor tendon injury, it is often associated with suboptimal outcomes and results in substantial digit dysfunction . To elucidate and characterize the intimate processes of flexor tendon injury and healing, animal models have been used and contributed to the emergence of new treatment options, which lead to reduced adhesion formation and improved digit function . To date, canine and chicken are the most widely used animal models for flexor tendon research .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While surgical repair serves as the standard procedure for flexor tendon injury, it is often associated with suboptimal outcomes and results in substantial digit dysfunction . To elucidate and characterize the intimate processes of flexor tendon injury and healing, animal models have been used and contributed to the emergence of new treatment options, which lead to reduced adhesion formation and improved digit function . To date, canine and chicken are the most widely used animal models for flexor tendon research .…”
mentioning
confidence: 99%
“…4,5 To elucidate and characterize the intimate processes of flexor tendon injury and healing, animal models have been used and contributed to the emergence of new treatment options, which lead to reduced adhesion formation and improved digit function. 5,6 To date, canine and chicken are the most widely used animal models for flexor tendon research. [7][8][9] However, they possess several disadvantages that limit the translation of experimental findings into clinic applications, thus mandating the development of an alternative animal model.…”
mentioning
confidence: 99%
“…Ji et al recently reported that autograft tendon treated with cd‐SNY‐gelatin improved digit function without any conjunction rupture at either proximal or distal repair after 6 weeks of tendon reconstruction. Zhao et al, however, reported a 28% distal rupture rate for allograft treated with carbodiimide‐derivatized hyaluronic acid and gelatin (CHG) and 14% for allograft alone for flexor tendon reconstruction at 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…After cell seeding, the tendon was treated with cd‐SYN of the following formula: 46% native synovial fluid, 10% gelatin (Sigma), 1% 1‐ethyl‐3‐([3‐dimethylaminopropyl] carbodiimide hydrochloride) (Sigma), and 1% N‐hydroxysuccinimide (Sigma) in 0.1 M of 2‐[N‐morpholino] ethanesulfonic acid buffer (Sigma) (pH, 6.0). The ratio of the cd‐SYN was also based on the previous publication …”
Section: Methodsmentioning
confidence: 99%
“…Animal models of flexor tendon injuries are commonly used for in vivo and in vitro studies, which aid in our understanding of tendon abnormalities and allow for development of novel therapeutic options . The most widely used animal models are the canine forepaw and the chicken foot, each possessing their own advantages and disadvantages.…”
mentioning
confidence: 99%